The Important Evidence of Leverage in Mediating the Effect of Sales Growth and Capital Intensity on Profitability - Sarah Triayuni; Najmudin; Rio Dhani Laksana (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The main goal of this study is to assess the impact of sales growth applying the leverage as mediator factor and capital intensity to profitability. The population of study consist of 41 manufacture corporates registered at the IDX which the observation period during year 2019 to 2020. Based on the data analysis and result of study applying Structural Equation Modeling-Partial Least Square or SEM-PLS, the evidence shows that there is no impact significantly from sales growth to profitability. Meanwhile, sales growth has an impact positively to leverage; financial leverage has an impact negatively to profitability; and financial leverage could mediate the effect of sales growth variable to profitability. In addition, capital intensity has an impact negatively to profitability.As the implication, this result recommends that manufacture companies should avoid using debt to finance their operation because it could lead to a decrease in profits.